THE APPLICATION PROBLEM BASED LEARNING APPROACH WITH PICTURE MEDIA TO EXPLANATION TEXT WRITING LEARNING FOR JUNIOR HIGHSCHOOL STUDENT - Suparna Suparna (IKIP Siliwangi, 2021)
The purpose of this study is to describe problem-based learning steps with the help of image media in the learning of explantation writing and writing results before and after the implementation of learning in control and experiment classes.The research location was conducted at SMP Negeri 1 Bungursari Purwakarta in the 2019/2020 school year.The research method used is an experimental method with the design of a kuasi experiment.The research procedure is carried out with three stages, namely the implementation of the initial test of writing explantation text, the implementation of problem based learning with the help of image media in the experimental class while in the control class of problem based learning implementation only and the final test of writing explantation.The sampling technique used is purposive sampling based on the similarity of the student's cognitive level.The selected samples are grade VIII A students as experimental classes and grade VIII.B as control classes..Data analysis is done with quantitative data analysis with the help of SPSS 20.0 and Microsoft Excel 2013 programs. The results of the study show that the implementation of problem-based learning with the help of image media in learning can be done with the following stages, namely: 1) the introduction of learning with the delivery of the objectives of writing explantation learning; 2) formation of study groups; 3) providing explantation text stimulus facilitated by teachers by providing stimulus with image media; 3) identify problems with the exoplanet text in the image; 4) group and process data to answer questions; 5) convey the results of the discussion, and 6) conclude the learning.The results of writing were obtained that the improvement of writing ability of students whose learning using problem-based learning approach with the help of image media is better than those using problem based learning approach only.This is seen from the average difference test significance value below 0.05.